Strong Impact of Smoking on Multimorbidity and Cardiovascular Risk Among Human Immunodeficiency Virus-Infected Individuals in Comparison With the General Population. (8th July 2015) - Hasse, Barbara; Tarr, Philip E.; Marques-Vidal, Pedro; Waeber, Gerard; Preisig, Martin; Mooser, Vincent; Valeri, Fabio; Djalali, Sima; Andri, Rauch; Bernasconi, Enos; Calmy, Alexandra; Cavassini, Matthias; et al.
Abstract : AIDS-associated morbidity has diminished due to excellent viral control. Multimorbidity are more prevalent and incident in Swiss HIV-positive persons compared to HIV-negative controls. However, smoking, but not HIV status, had a strong impact on cardiovascular risk and multimorbidity. Abstract: Background.  Although acquired immune deficiency syndrome-associated morbidity has diminished due to excellent viral control, multimorbidity may be increasing among human immunodeficiency virus (HIV)-infected persons compared with the general population. Methods.  We assessed the prevalence of comorbidities and multimorbidity in participants of the Swiss HIV Cohort Study (SHCS) compared with the population-based CoLaus study and the primary care-based FIRE (Family Medicine ICPC-Research using Electronic Medical Records) records. The incidence of the respective endpoints were assessed among SHCS and CoLaus participants. Poisson regression models were adjusted for age, sex, body mass index, and smoking. Results.  Overall, 74 291 participants contributed data to prevalence analyses (3230 HIV-infected; 71 061 controls). In CoLaus, FIRE, and SHCS, multimorbidity was present among 26%, 13%, and 27% of participants. Compared with nonsmoking individuals from CoLaus, the incidence of cardiovascular disease was elevated among smoking individuals but independent of HIV status (HIV-negative smoking: incidence rate ratio [IRR] = 1.7, 95% confidence interval [CI] = 1.2–2.5; HIV-positive smoking: IRR = 1.7, 95% CI = 1.1–2.6; HIV-positive nonsmoking: IRR = 0.79, 95% CI = 0.44–1.4). Compared with nonsmoking HIV-negative persons, multivariable Poisson regression ide.jpegied associations of HIV infection with hypertension (nonsmoking: IRR = 1.9, 95% CI = 1.5–2.4; smoking: IRR = 2.0, 95% CI = 1.6–2.4), kidney (nonsmoking: IRR = 2.7, 95% CI = 1.9–3.8; smoking: IRR = 2.6, 95% CI = 1.9–3.6), and liver disease (nonsmoking: IRR = 1.8, 95% CI = 1.4–2.4; smoking: IRR = 1.7, 95% CI = 1.4–2.2). No evidence was found for an association of HIV-infection or smoking with diabetes mellitus. Conclusions.  Multimorbidity is more prevalent and incident in HIV-positive compared with HIV-negative individuals. Smoking, but not HIV status, has a strong impact on cardiovascular risk and multimorbidity.